Education To Improve The Healthy Life Of Rural Communities In Accelerating The Reduction Of Stunting - Nasrudin, Nasrudin; Prisusanti, Retno Dewi; Syofya, Heppi; Maidelwita, Yani; Yuliati, Luluk (Journal Of Human And Education (JAHE), 2024)
This dedication began with the author's concern about the stunting rate in Indonesia, which is large and even tends to increase every year. Therefore, the authors, who happen to have had a relationship for a long time, discussed providing education to the closest rural communities, in this case the villages of Village in Medan, Sumber Sekar Village, Malang, Air Pacah Village, West Sumatra, and Gerit Village in Patih to educate about healthy lifestyles to reduce stunting in collaboration with community health centers and local health workers. The results in this research show 1). This dedication began with the writer and community service's concern for the stunting rate which continues to increase every year, one of the biggest contributors to stunting, comes from rural areas. 2). A healthy lifestyle can reduce stunting rates and the authors agree to provide education on healthy lifestyles to rural communities, especially mothers in the nearest villages, namely Amplas Medan Village health center, Sumber Sekar Village, Malang, Air Pacah Village, West Sumatra, and Gerit Village in Patih . 3). Education contains 11 materials which are repeated 2-3 times within one month with variations of 1 theory and 1 practice in the theme of material that can be put into practice.